The impact of government regulation on the Russian competitiveness within global “green” economy in conditions of sanctions - E. S. Novikova; E. V. Golubtsova (Вестник университета)
The aim of this paper is the study of the impact of state tax regulation on the competitiveness level of the Russian economy taking into account the development of “green” initiatives in the current conditions of sanctions pressure. This research includes the analysis of current positions of key countries promoting the initiative of “green” economy at the global level, and key beneficiaries of implemented mechanism are considered. Additionally, the situation in the Russian economy has been outlined within the global “green” economy with suggestions of the most efficient position for the national economy within the current situation. Moreover, this research includes the analysis of “green” economy concept development, its promotion and implementation by countries with the usage of different indicators for results measuring of economies by global “green” rankings.